Physics Problem Solving Skills with IBL-STEMWeb: Students on Small Islands in Maluku - Jamaludin Jamaludin; John Rafafy Batlolona (Jurnal Penelitian Pendidikan IPA, 2022)
Learning on small islands in Maluku still has many obstacles. It is limited by inadequate supporting facilities and infrastructure in the form of internet availability in accessing learning materials. Maluku's natural resources, both biological and non-biological, are very abundant. However, they have not been managed properly in improving the community's welfare. Therefore, education is one of the spearheads in improving the quality of students so that they can manage the existing nature well in the future. One of the recommended lessons is IBL-STEWeb to improve the academic quality of students. The use of IBL-STEWeb can take into account the involvement of students' preconceptions, provide in-depth basic knowledge, help students make connections within the context of a conceptual framework, and can map students' knowledge in a way that facilitates the search and application of information